The differential sensitivity of the hypothalamic–hypophysial–ovarian axis to 5‐hydroxytryptophan alters the secretion of estradiol - Juana Monroy; Omar D. Cortés; Roberto Domínguez; María Eugenia Mendoza‐Garrido; Eloir Gallegos; Mario Cárdenas; Andrés Aragón; María E. Ayala (Experimental Physiology, 2024)
Abstract Serotonin [5‐hydroxytryptamine (5‐HT)] modulates ovarian function. The precursor of 5‐HT, 5‐hydroxytryptophan (5‐HTP), has been used to treat depression. However, the effects of 5‐HTP on ovarian and reproductive physiology remain unknown. In this research, we analysed the impact of 5‐HTP on the monoaminergic system and its interactions with the reproductive axis and ovarian estradiol secretion when administered by distinct routes. Female rats 30 days of age were injected with 5‐HTP i.p. (100 mg/kg), into the ovarian bursa (1.5 µg/40 µL) or into the median raphe nucleus (20 µg/2.5 µL) and were killed 60 or 120 min after injection. As controls, we used rats of the same age injected with vehicle (0.9% NaCl). Monoamine, gonadotrophin and steroid ovarian hormone concentrations were measured. The injection of 5‐HTP either i.p. or directly into the ovarian bursa increased the concentrations of 5‐HT and the metabolite 5‐hydroxyindole‐3‐acetic acid in the ovary. For both routes of administration, the serum concentration of estradiol increased. After i.p. injection of 5‐HTP, the concentrations of luteinizing hormone were decreased and follicle‐stimulating hormone increased after 120 min. Micro‐injection of 5‐HTP into the median raphe nucleus increased the concentrations of 5‐HT in the anterior hypothalamus and dopamine in the medial hypothalamus after 120 min. Our results suggest that the administration of 5‐HTP either i.p. or directly into the ovarian bursa enhances ovarian estradiol secretion.